Changes in Moisture entering the atmosphere of Iran and its relationship with seasonal wet and dry periods - Mostafa Karimi; Mahnaz Jafari; Faramarz Khosh Akhlgh; Saeed Bazgir (تحقیقات کاربردی علوم جغرافیایی)
Spatio-temporal variations of factors affecting the occurrence of precipitation can lead to a change in its amount. The atmospheric moisture is one of the most important factors for precipitation formation. In this study, changes in atmospheric moisture and its relation with occurrence of seasonal wet and dry periods were investigated in Iran. The re-analysis data from the ERA interim European Center for Mid-Term Projections (ECMWF) was used during the period 1981-2011. The z index (ZSI) was used to extract wet and dry periods of autumn, winter and spring seasons. The seasons with the maximum percentage of wetness/drought occurrence during the above periods were selected. Vertical integrated divergence of the moisture flux was extracted in three layers of the lower, middle and upper atmosphere above Iran. The results revealed that in all three layers, moisture flux was maximum during wet period and decreased in dry one. In all layers in wet and dry periods, the moisture content imported to Iran increased during warm season as compared to cold seasons. In addition, the difference in moisture content in the warm season was less than cold seasons and has less variations. There was no significant changes in moisture at high levels in three seasons. In general, there was a significant difference in terms of the winds pattern in the wet and dry periods. The favorable conditions of flow patterns on the water surface of the region provide the condition for increasing transport of moisture to Iran. Although, the moisture transfer reduced due to deviation and change of direction of currents, in dry period especially in the lower layer, and hence increase the occurrence of dry periods in Iran.